2016
DOI: 10.1111/jmi.12403
|View full text |Cite
|
Sign up to set email alerts
|

Making microscopy count: quantitative light microscopy of dynamic processes in living plants

Abstract: Summary Cell theory has officially reached 350 years of age as the first use of the word ‘cell’ in a biological context can be traced to a description of plant material by Robert Hooke in his historic publication ‘Micrographia: or some physiological definitions of minute bodies’. The 2015 Royal Microscopical Society Botanical Microscopy meeting was a celebration of the streams of investigation initiated by Hooke to understand at the subcellular scale how plant cell function and form arises. Much of the work pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…On the other hand, such diversity also brings about the fragmentation of the community regarding tools of choice and, more importantly, file and data formats. Advances in the state-of-the-art allow us to observe biological phenomena at different scales and complexities from single molecule to whole organs [58,59]. It is of paramount importance to agree on file and data standards within the community that maximise transferability of both raw image and processed data, such that we can increase power, accuracy and efficiency of quantification protocols.…”
Section: Quantitative Image Analysismentioning
confidence: 99%
“…On the other hand, such diversity also brings about the fragmentation of the community regarding tools of choice and, more importantly, file and data formats. Advances in the state-of-the-art allow us to observe biological phenomena at different scales and complexities from single molecule to whole organs [58,59]. It is of paramount importance to agree on file and data standards within the community that maximise transferability of both raw image and processed data, such that we can increase power, accuracy and efficiency of quantification protocols.…”
Section: Quantitative Image Analysismentioning
confidence: 99%
“…Over the years, they have earned a reputation as being one of the most useful and interesting venues for researchers involved in the microscopical study of plant cells and tissues. As noted by Fricker et al (2016), we botanists have a proud history that goes back 350 years to some of the earliest microscopical investigations ever made. In 1665, Robert Hooke, upon observing small compartments in cork tissue, coined the term "cell", which is recognized as the basic building block of all living organisms.…”
Section: Introduction 10th International Botanical Microscopy Meetingmentioning
confidence: 99%
“…An important goal for all microscopical studies is to provide quantitation of the structures and events being observed. Fricker et al (2016) address this directly and provide an overview of computational approaches for gleaning quantitative data from our many micrographs. Many different programs and associated analytical tools are noted and brief summaries of how they can help are provided.…”
Section: Introduction 10th International Botanical Microscopy Meetingmentioning
confidence: 99%
See 1 more Smart Citation